Influence of Symmetry on the Magneto-Optical Properties of a Bifunctional Macrocyclic Dyiii Complex - Aravena-Ponce, D; Aravena-Ponce, D (Royal Society of Chemistry, 2023)
In this work, a novel complex, [Dy(LPr)(NO3)2]·(H2O)·(NO3) (1), containing a highly distorted macrocyclic ligand (LPr) and weak axial anions (NO3−), was synthesized and characterized. Even though this coordination environment is not ideal for maximizing the magnetic anisotropy of a DyIII ion, a magneto-structural analysis reveals that the high distortion of the macrocycle promotes a disposition of the hard plane and easy axis opposite to the expected one. This results in a quite symmetrical environment which allows obtaining a field induced SMM behaviour. The magnetic relaxation properties of this complex were rationalized with the aid of ab initio multireference calculations. Moreover, 1 showed the characteristic emission bands of DyIII ion, indicating that the macrocyclic ligand acts as an efficient sensitizer in the energy transfer process to the emissive state of the DyIII ion. Due to the symmetric environment of 1, the Y/B intensity ratio (0.61) results in CIE coordinates (0.278; 0.314), close to those of the white light region. To gain further insight into the mechanism leading to the luminescence properties, ab initio calculations were performed to elucidate the key factors controlling the Y/B intensity ratio in this bifunctional complex. © 2023 The Royal Society of Chemistry.